2018
DOI: 10.1002/jbm.a.36565
|View full text |Cite
|
Sign up to set email alerts
|

Differences in biocompatibility of microneedles from cyclic olefin polymers with human endothelial and epithelial skin cells

Abstract: Microneedles are promising devices for transdermal delivery and diagnostic applications, due to their minimally invasive and painless nature of application. However, so far, applications are limited to small scale research projects. Material selection and production for larger projects remain a challenge. In vitro testing using human cell culture could bridge the gap between cost effective screening of suitable materials and concerns for safety and ethics. In this study, materials were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The obtained results suggested that the octagonal pyramidal MNs can be an effective tool in developing novel intradermal drug delivery systems [77]. Recently, Schossleitner et al investigated the biocompatibility of MNs from cyclic olefin polymers [78]. In this study, epithelial and human endothelial cells were used for testing with the elution method and the direct contact method.…”
Section: Biocompatibility Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…The obtained results suggested that the octagonal pyramidal MNs can be an effective tool in developing novel intradermal drug delivery systems [77]. Recently, Schossleitner et al investigated the biocompatibility of MNs from cyclic olefin polymers [78]. In this study, epithelial and human endothelial cells were used for testing with the elution method and the direct contact method.…”
Section: Biocompatibility Analysismentioning
confidence: 96%
“…The results demonstrated that the elution method of inflammatory markers revealed no negative effects in applied tests, whereas the assessment of differentiation markers on cells in direct contact with the material showed differences, and thus, can help to identify the preferred materials for future medical devices. The study also proposed that the elution-based biocompatibility testing cannot give the complete picture and additional advanced staining techniques and cell types specific for the application of the medical device can improve material selection for the devices [78]. Moussi et al conducted the cytotoxicity analysis to determine the biocompatibility of 3D-printed MNs [79].…”
Section: Biocompatibility Analysismentioning
confidence: 99%
“… Patient ease of use and reliability: without risks, patients should be able to use the goods as possible [ 77 , 84 ]; Correct delivery insertion: since MN injection does not induce discomfort or apparent emotion, the patient has no feedback. A proper program framework may be appropriate [ 381 , 382 , 383 ]; Repetitive use of immunological effects: repeated insertion of MN into the skin may cause immune reactions. The regulators should be assured of immunological protection [ 139 , 384 , 385 ]; Profile for long-term security: to date, human volunteers have conducted short-term security experiments.…”
Section: Regulatory Issues With Polymeric Microneedlesmentioning
confidence: 99%
“…Also, the maximisation test was performed to assess the primary skin irritation [70]. Recently, Schossleitner et al investigated the biocompatibility of MNs from cyclic olefin polymer [71]. In this study, epithelial and human endothelial cells were used for testing with the elution method and the direct contact method.…”
Section: Biocompatibility Analysismentioning
confidence: 99%
“…The evaluations were done on the basis of cell viability, morphology, cellular differential and barrier formation. The team also used inflammatory markers such as E-Selectin and ICAM-1 to assess immune cell adhesion potential [71]. Moussi et al conducted the cytotoxicity analysis to determine the biocompatibility of 3D printed MNs [72].…”
Section: Biocompatibility Analysismentioning
confidence: 99%